2000
DOI: 10.1038/sj.bjp.0703703
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin‐sensitive Gi‐proteins and intracellular calcium sensitivity of vasoconstriction in the intact rat tail artery

Abstract: 1 We studied the involvement of pertussis toxin (PTX)-sensitive G-proteins in the sensitivity of arterial constriction to intracellular calcium ([Ca 2+ ] i ) mobilization. 2 Vasoconstriction was measured in vitro in perfused, de-endothelialized rat tail arteries loaed with the calcium-sensitive dye, fura-2 and treated or not with PTX (30 ± 1000 ng ml 71 ). Arteries were stimulated with noradrenaline (NA, 0.1 ± 100 mM) or KCl (15 ± 120 mM). 3 KCl elicited a smaller vasoconstrictor response (E max =94+8 mmHg) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…i and inhibit forskolin-stimulated cAMP accumulation with similarly high potency via G␣ q and G␣ i , respectively (Brighton et al, 2004b). Although we have not explored the signaling consequences of G␣ I coupling in smooth muscle cells, previous studies have suggested that G␣ i can contribute significantly to agonist-mediated contractile events (Spitzbarth-Régrigny et al, 2000), and this would be consistent with offsetting cAMP-mediated relaxation. Although there are clearly exceptions, peripheral tissue generally expresses NmU-R1, whereas NmU-R2 is generally expressed within the central nervous system, suggesting that the NmU receptor involved here is likely to be NmU-R1 (see Brighton et al, 2004a).…”
Section: Discussionmentioning
confidence: 91%
“…i and inhibit forskolin-stimulated cAMP accumulation with similarly high potency via G␣ q and G␣ i , respectively (Brighton et al, 2004b). Although we have not explored the signaling consequences of G␣ I coupling in smooth muscle cells, previous studies have suggested that G␣ i can contribute significantly to agonist-mediated contractile events (Spitzbarth-Régrigny et al, 2000), and this would be consistent with offsetting cAMP-mediated relaxation. Although there are clearly exceptions, peripheral tissue generally expresses NmU-R1, whereas NmU-R2 is generally expressed within the central nervous system, suggesting that the NmU receptor involved here is likely to be NmU-R1 (see Brighton et al, 2004a).…”
Section: Discussionmentioning
confidence: 91%
“…NO‐mediated activation of phosphorylated myosin light chain (P‐MLC) phosphatase may be involved [27]. In another experiment, we have shown, using pertussis toxin, a G‐protein inhibitor, and tautomycine, a phosphatase inhibitor, that amplification of agonist‐evoked contraction via inhibition of P‐MLC phosphatase is a membrane receptor‐mediated event [28]. This reinforces the argument that a receptor‐mediated event is involved in the effects of melatonin observed in the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the significance of singular knockouts is limited by overlapping functions of these isoforms. Pertussis toxin (PTX) has been used to study G i protein signaling in the cardiovascular system [7,8], but the effects on cerebrovasculature have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, PTX irreversibly and with high specificity blocks G i -linked GPCR signal transduction -hereafter referred to as non-cerebral G i PCR KO -by catalyzing covalent modification of a C-terminal cysteine residue of cellular Gα i isoforms [9][10][11]. In arteries and microvessels, PTX inhibits endothelium-dependent relaxation to certain agonists such as β-adrenergic ligands, angiotensin, serotonin, or relaxins and is therefore useful for the study of vasculopathies [2,7,8,[12][13][14][15][16][17][18]. We have previously demonstrated that PTX, administered in a single peritoneal injection, does not cross the blood-brain barrier (BBB) and does not modify G i PCR signaling in neurons [19].…”
Section: Introductionmentioning
confidence: 99%